2018
DOI: 10.1159/000487975
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Long Noncoding RNA and mRNA Expression Profiles in IL-9-Activated Astrocytes and EAE Mice

Abstract: Background/Aims: Multiple sclerosis (MS) is an autoimmune disease in the central nervous system associated with demyelination and axonal injury. Astrocyte activation is involved in the pathogenesis of MS and experimental autoimmune encephalomyelitis (EAE), an animal model of MS. This study was designed to find potential lncRNAs in EAE mice and activated astrocytes. Methods: we performed microarray analysis of lncRNAs from the brain tissues of EAE mice and primary mouse astrocytes treated with IL-9(50 ng/ml). 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Total RNA was extracted from astrocytes and hippocampal tissues according to manufactures instructions. Reverse transcription and real-time PCR (qPCR) assay was performed as previously described [47]. The sequences of primers are listed in Additional file 1: Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from astrocytes and hippocampal tissues according to manufactures instructions. Reverse transcription and real-time PCR (qPCR) assay was performed as previously described [47]. The sequences of primers are listed in Additional file 1: Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…The expression profiles of lncRNAs and mRNAs were detected as previously described [ 49 ]. Primary mouse astrocytes treated with 50 ng/ml Nef protein (Abcam, ab90462) were detected using Mouse LncRNA Microarray v2.0 (8 × 60 K, Arraystar) by Kangchen Bio-tech (Shanghai, China) that designed for the global profiling of mouse LncRNAs and protein-coding transcripts.…”
Section: Methodsmentioning
confidence: 99%
“…Real-time PCR (real-time PCR) assay was detected as previously described [ 49 ]. In brief, the total RNA from cultured astrocytes was extracted with TRIzol reagent (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the study was unable to identify differential expression of either the lncRNA candidate or its associated gene, significant correlation between lnc-IL-7R and IL-7Ra were seen in both MS and healthy groups. These studies suggest a potential functional role of lncRNA transcripts in regulation of gene targets in MS. Several studies using animal models have also considered the role of lncRNAs in MS pathogenesis (Duan et al, 2018;Guo et al, 2017;Li et al, 2018;Liu et al, 2018;Sun et al, 2017), or combinations of human participants and animal model studies (Masoumi et al, 2019;Pahlevan Kakhki et al, 2018). These studies have demonstrated the role of multiple lncRNA transcripts in differentiation of CD4 + T cell linages.…”
Section: Introductionmentioning
confidence: 99%